Recently Applications of tert-butyl Nitrite in Organic Synthesis-Part I - Ghaffari Khaligh, Nader (Current Organic Chemistry, 2018)
This mini-review will describe the recent applications of tert–butyl nitrite (TBN) in organic synthesis. Due to its unique structural feature and wide application, TBN holds a prominent and great potential in organic synthesis. Since the applications of TBN is too wide and developments have been too fast, Part-I of the present mini-review has surveyed the studies carried out to date in three areas viz. aerobic oxidation, annulation, and diazotization, which is demonstrated by the work outlined in this mini-review. The mechanisms of these transformations will be briefly described in this mini-review. TBN has been utilized in other organic transformations, such as nitrogenation, nitrification, nitrosylation, multifunctionalization, nitrodecarbocyclization, nitro-aminoxylation and etc. which will be presented as part- II in mid-2018.
Keywords: aerobic oxidation